BOILING TECHNIQUE AS A WAY OF PROCESSING ANTIDIABETIC MEDICINAL PLANTS OF THE ANAK TRIBE IN THE KIJANG RIVER, ULU RAWAS DISTRICT - Fitria Lestari1*, Yuli Febrianti2, Ivoni Susanti3, Agus Andriansah4, Frengky Alexander Pratama5, (Chelonian Research Foundation, 2023)
The tributary tribe in the Kijang River is a tribe that is scattered and found in the hamlet of Sungai Kijang, Rawas Ulu district, and for generations has carried out treatment using plants, such as treating diabetes whose sufferers do not look at age. People generally treat this disease by consuming synthetic drugs that for a long time have side effects for other parts of the body. Therefore, proper processing of medicinal plants can be a solution to minimize the side effects of synthetic drugs. The method used in the study used the cruising method with observation techniques, interviews with the head of the Deer River tribe, the use of primary sources, and documentation. The results of exploring the forest along the Antelope River for approximately 1 month show that the boiling technique is a technique that is often used by the Anak tribe in processing plants into antidiabetic drugs. It is concluded that nature has great potential to prevent, treat, and also as the body's immune system from disease. Keywords: antidiabetic, boiling, Orang Rimba (Orang Rimba Tribe), Sungai Kijang